Quality of life after transcatheter aortic valve implantation and surgical replacement in high-risk elderly patients - Kala, Petr; Tretina, Martin; Poloczek, Martin; Ondrasek, Jiri; Malik, Petr; Pokorny, Petr; Parenica, Jiri; Spinar, Jindrich; Jarkovsky, Jiri; Littnerova, Simona; Nemec, Petr (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
AIM: The aim of this study was to compare the quality of life after transcatheter aortic valve implantation (TAVI) and surgical replacement (SAVR) at one year. METHODS: The study included 45 consecutive high-risk patients (average age 82.0 years; logistic Euroscore 22.3%) with symptomatic severe aortic stenosis allocated to TAVI transfemoral, TAVI transapical using the Edwards-Sapien valve or SAVR with the Edwards Perimount bioprosthesis (n=15 in each). The pre-operative characteristics were similar except for more myocardial infarctions in TAVI. The quality of life was assessed using the standardized EQ-5D questionnaire at baseline and on days 30, 90 and 360. The protocol was approved by the local ethics committee and an informed consent was signed. A total of 7 patients (15.5%) died during follow-up. RESULTS: At baseline no significant differences in any of the quality-of-life parameters were found except for usual activities described as "best" (46.7% in SAVR vs. 10.0% in TAVI; P=0.002). At 30 and 90 days surviving patients were similar and at 360 days only the anxiety/depression score was "best" in 83.3% SAVR vs. 59.1% (P=0.046). Functional status improved in all patients (NYHA class I-II in 13.3% at baseline vs. 78.9% at 360-days) and the general health median significantly improved in TAVI patients (from 50 to 67; P=0.001) with a positive trend in SAVR patients (P=0.060). CONCLUSIONS: At one year, the general quality of life of high-risk patients had significantly improved after transcatheter aortic valve implantation with a positive trend in surgically treated patients.
Keywords: Surveys and Questionnaires; aortální stenóza; Humans; Quality of Life; Female; rizikové faktory; chirurgická náhrada chlopně; Aged; výsledek terapie; senioři; lidé; Aortic Valve Stenosis; kvalita života; Heart Valve Prosthesis; průzkumy a dotazníky; ženské pohlaví; Male; prognóza; Treatment Outcome; Aged, 80 and over; srdeční katetrizace; Cardiac Catheterization; senioři nad 80 let; srdeční chlopně umělé; Risk Assessment; mužské pohlaví; Heart Valve Prosthesis Implantation; hodnocení rizik; Prognosis; Risk Factors